Towards a strategic alignment of public health and primary care practices at local levels – the case of severe and enduring mental illness - Banarsee, Ricky (London J Prim Care (Abingdon), 2018)
The rapidly increasing number of people who have long-term conditions requires a system of coordinated support for self-care throughout the NHS. A system to support self-care needs to be aligned to systems that support shared-care and community development, making it easier for the multidisciplinary teams who provide care to also help patients and populations to help themselves. Public health practitioners need to work closely with clinicians to achieve this. The best place to coordinate this partnership is a community-based coordinating hub, or local health community – a geographic area of about 50,000 population where different contributions to self-care can be aligned. A shared vision for both health and disease management is needed to ensure consistent messaging by all. A three tier system of shared care can help to combine vertical and horizontal integration. This paper uses severe and enduring mental illness as an exemplar to anticipate the design of such a system.